2020
DOI: 10.1186/s13578-020-00400-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum IP-10 and IL-17 from Kawasaki disease patients induce calcification-related genes and proteins in human coronary artery smooth muscle cells in vitro

Abstract: Background: Kawasaki disease (KD) is one of the major causes of heart disease and vasculitis in children under 5 years old in the world. Clinical evidence has shown that coronary artery calcification may develop in KD patients, however the mechanism has not been elucidated. Previous studies have found that interferon-γ-inducible protein (IP)-10 and interleukin (IL)-17 can be elevated and may play a role in KD development and coronary artery lesion formation. The purpose of this in vitro study was to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…HCASMCs treated with CXCL10 and IL-17 developed a phenotype that could promote vascular calcification in a path similar to the bone morphogenetic protein (BMP) 6 autocrine pathway. Furthermore, the BMP6 autocrine stimulation in CXCL10 and IL-17-treated HCASMCs could up regulate the activation of smad1/five-runx2 signaling and increase the bone matrix-related proteins including the osteopontin, osteocalcin and alkaline levels [80]. Lupieri and co-workers [81] demonstrated an unexpected cellular cross-communication in the arterial endothelial cells where a phosphatidylinositide 3-kinase (PD3K)-dependent T cell response resulted in CXCL10 production by smooth muscle cells inhibiting endothelial repairs.…”
Section: Mechanism Of the Cxcl10 Action In Cadmentioning
confidence: 99%
See 1 more Smart Citation
“…HCASMCs treated with CXCL10 and IL-17 developed a phenotype that could promote vascular calcification in a path similar to the bone morphogenetic protein (BMP) 6 autocrine pathway. Furthermore, the BMP6 autocrine stimulation in CXCL10 and IL-17-treated HCASMCs could up regulate the activation of smad1/five-runx2 signaling and increase the bone matrix-related proteins including the osteopontin, osteocalcin and alkaline levels [80]. Lupieri and co-workers [81] demonstrated an unexpected cellular cross-communication in the arterial endothelial cells where a phosphatidylinositide 3-kinase (PD3K)-dependent T cell response resulted in CXCL10 production by smooth muscle cells inhibiting endothelial repairs.…”
Section: Mechanism Of the Cxcl10 Action In Cadmentioning
confidence: 99%
“…Zuojun and co-workers demonstrated that CXCL10 plays an important role in intimal hyperplasia as siRNA-mediated CXCL10 silencing inhibited aberrant VSMC hyperplasia and reduced restenosis in atherosclerotic patients [78,79]. In vitro studies of human coronary artery smooth muscle cells (HCASMCs) performed by Chang [80] showed a functional role for plasma-circulating CXCL10 and IL-17 in the development of vascular calcification and revealed its underlying mechanism in cardiovascular disease. HCASMCs treated with CXCL10 and IL-17 developed a phenotype that could promote vascular calcification in a path similar to the bone morphogenetic protein (BMP) 6 autocrine pathway.…”
Section: Mechanism Of the Cxcl10 Action In Cadmentioning
confidence: 99%
“…This is reminiscent of the Toxic Shock (TSS) -Kawasaki syndrome phenotype currently being considered as PMIS/MIS-C syndrome (35)(36)(37)(38)(39). Similar to TSS and Kawasaki's, our PedSep-C patients showed elevated IL-17a and IP10/CXCL10 levels (40)(41)(42).…”
Section: Discussionmentioning
confidence: 59%
“…KD is acute, systemic, nonspeci c, self-limiting vasculitis. Its adverse effects depend mainly on the incidence of CALs, including coronary artery dilation, coronary aneurysm, thrombosis, myocardial ischemia, and even sudden death [7,8]. Intravenous immunoglobulin (IVIG) is one of the rst-line drugs used to treat KD.…”
Section: Discussionmentioning
confidence: 99%
“…It exerted a recruiting and chemotactic effect on T cells in autoimmune diseases and aggregated the corresponding T cells to target organs, causing tissue and organ damage [19]. IP-10/IL-17 secreted from the plasma of pediatric patients with KD acted on the calci cation of human coronary artery smooth muscle cells (HCASMCs); IL-17 might also interact with IFN-g to enhance the production of IP-10 [8]. Thus, it was inferred that IP-10 and IL-17A cooperatively in uenced the CALs in KD.…”
Section: Discussionmentioning
confidence: 99%